2002
DOI: 10.1002/tcr.10030
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Aza‐Heterocycles from Oximes by Amino‐Heck Reaction

Abstract: Oxidative addition of oximes to palladium(0) complexes generates alkylideneaminopalladium(II) species, which are utilized as key intermediates for carbon-nitrogen bond formation. Various aza-heterocycles, such as pyrrole, pyridine, isoquinoline, spiroimine, and azaazulene, can be synthesized from O-pentafluorobenzoyloximes having an olefinic moiety via an intramolecular Heck-type reaction (amino-Heck reaction) by treatment with a catalytic amount of a Pd(0) complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…[36] In this radical cyclization, copper powder gradually reacted with 1,2-dichloroethane to generate the copper() salt, which acts as an active redox catalyst. (21) Amino-Heck Reaction [37] As lower-valent palladium compounds are good electron donors, oxime derivatives were expected to react with Pd 0 complexes, giving oxidative addition compounds, alkylideneaminometal species. In fact, an equimolar amount of 4,4Ј-bis(trifluoromethyl)benzophenone O-(methylsulfonyl) oxime (71) and Pd(PPh 3 ) 4 reacted in tetrahydrofuran (THF) at room temperature, and, after quenching with a pH 9 buffer, 4,4Ј-bis(trifluoromethylphenyl)methylideneamine (73) was obtained as a crude product.…”
Section: Radical Cyclizationmentioning
confidence: 99%
“…[36] In this radical cyclization, copper powder gradually reacted with 1,2-dichloroethane to generate the copper() salt, which acts as an active redox catalyst. (21) Amino-Heck Reaction [37] As lower-valent palladium compounds are good electron donors, oxime derivatives were expected to react with Pd 0 complexes, giving oxidative addition compounds, alkylideneaminometal species. In fact, an equimolar amount of 4,4Ј-bis(trifluoromethyl)benzophenone O-(methylsulfonyl) oxime (71) and Pd(PPh 3 ) 4 reacted in tetrahydrofuran (THF) at room temperature, and, after quenching with a pH 9 buffer, 4,4Ј-bis(trifluoromethylphenyl)methylideneamine (73) was obtained as a crude product.…”
Section: Radical Cyclizationmentioning
confidence: 99%
“…Recently, Narasaka reported that homoallyl ketone O-pentafluorobenzoyloximes underwent oxidative addition to Pd(0) to generate alkylideneaminopalladium species, which afforded nitrogen heterocycles via the insertion of an alkene moiety in a 5-exo fashion [15]. This prompted us to investigate the 5-endo insertion of an intramolecular difluoroalkene moiety in 3,3-difluoroallyl ketone O-pentafluorobenzoyloximes 15, which provides a synthetic method for ring-fluorinated 3H-pyrrole derivatives 16 (Scheme 8).…”
Section: Heck-type 5-endo-trig Cyclizations With Aminopalladium Speciesmentioning
confidence: 99%
“…After removal of the solvent under reduced pressure, the residue was purified by recrystalization from hexane to give 20a (0.80 g, 64%) as white needles. 1 (15), c = 23.707(6) Å , U = 1121.4(5) Å 3 , T = 120(2) K, space group P2 1 /c, Z = 4, m(Mo Ka) = 0.107 mm À1 , 6907 reflections measured, 2186 unique (R int = 0.0158) which were used in all calculations. The final wR(F 2 ) was 0.3643 (all data).…”
Section: -(22-difluorovinyl)-2-methyl-34-dihydronaphthalen-1(2h)-omentioning
confidence: 99%
“…40 The intramolecular version of the Mizoroki Heck reaction has been widely used to construct a variety of ring systems. In general, the intramolecular Heck reaction prefers the exo mode cyclization, as the endo mode cyclization is less likely to form smaller rings (Scheme 21).…”
Section: Background To Alkene Insertionmentioning
confidence: 99%